Applying Carspecken's critical ethnography method to uncover the culture of health disparity in intensive care units - Sajad Yarahmadi; Mohsen Soleimani; Mohammad Gholami; Ali Fakhr-Movahedi; Seyed Mohsen Saeidi Madani (Tehran University of Medical Sciences, 2024)
Background & Aim: Carspecken's critical ethnography method has gained prominence in nursing research, necessitating a fresh perspective on its practicality and advantages. This study aims to provide a unique viewpoint on using critical ethnography as a foundational methodology to uncover health disparity culture in intensive care units. Methods & Materials: While emphasizing its review design with original examples, this perspective piece provides a practical explanation of Carspecken's five-stage critical ethnography approach. Grounded in the ontological and epistemological paradigm, this essay examines critical ethnography as a crucial approach to illuminating the discursive culture surrounding health disparities. Also, this study presents original instances of monological and dialogical data, reconstructive analysis, and findings from a study that was carried out to provide more perspective on implementation. It also mentions how it relates the findings to social factors and sociopolitical theories. Results: The study reveals nuanced insights into the practicality and advantages of Carspecken's method, shedding light on social processes contributing to health disparities in intensive care units. This method allowed us to identify how external powers extend to the intensive care unit, revealing a concealed culture that disrupts service provision balance. It exposed individual, organizational, and systemic roots contributing to disparities. Additionally, it highlighted how individual diversities can lead to disparity. Conclusion: This study highlights the significance of Carspecken's critical ethnography in nursing studies within the critical theory tradition. It is argued that Carspecken's approach to critical ethnography is particularly instrumental in elucidating the social structures contributing to health disparities.